From being teacher to teaching as a teacher: Social semiotics reconstruction of the educational activity - Claret Escalona, Mary (2017)
The article aims to demonstrate the social semiotics reconstruction of the educational activity based on the meaning and significance assigned by secondary school teachers, members of two educational institutions from Barquisimeto, Venezuela. The research was based on the qualitative approach of the interpretative paradigm, addressed from a phenomenological and hermeneutic perspective. Diverse oral speeches of social actors, who were selected in an opened and flexible manner, were obtained by means of an in-depth interview. By adopting an emerging and creative design, it was carried out an hermeneutic analysis, and we obtained diverse categories, among them we stand out: the vision of being a teacher; the process of being a teacher over time, the vocation of being a teacher in practice; mirrors to present themselves, putting up the image of a teacher; the beliefs of the teacher and others. As a reflection, this study draft various inner landscapes of the teachers to help us understand why it is important to investigate the being of the professional, his or her teaching praxis, exalting the status of the teacher, or now called master in this time of crisis and uncertainty that Latin America and specially Venezuela is living.